1999
DOI: 10.1111/j.1471-0528.1999.tb08265.x
|View full text |Cite
|
Sign up to set email alerts
|

The reasons for termination of pregnancy in the third trimester

Abstract: ObjectiveDesign Retrospective study. SettingPopulation A consecutive series of 956 terminations of pregnancy performed for fetal anomalies in singleton pregnancies, 305 of which were in the third trimester and 651 in the second. Main outcome measuresIndications for termination of pregnancy; process leading to late termination of pregnancy; maternal morbidity. ResultsOne hundred and thirteen (37%) third trimester terminations of pregnancy were associated with false negative resulted from the results of earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
46
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 7 publications
12
46
3
6
Order By: Relevance
“…Several other studies have reported previously a high prevalence of late TOPFA in France. 2,4,5 The variations in TOPFA rates in Europe have been reported previously. 1,5,6 In Paris, the second trimester anomaly scan tends to be performed later than in other European countries.…”
Section: Discussionsupporting
confidence: 64%
“…Several other studies have reported previously a high prevalence of late TOPFA in France. 2,4,5 The variations in TOPFA rates in Europe have been reported previously. 1,5,6 In Paris, the second trimester anomaly scan tends to be performed later than in other European countries.…”
Section: Discussionsupporting
confidence: 64%
“…Erken terminasyonların aksine geç terminasyonların en sık nedeni, fetal yapısal anomaliler olup, bunlar içinde en sık görülen fetal yapısal anomaliler MSS anomalileridir (9,11,14,15,16) . Hidrosefali, korpus kallosum agenezisi ve lizensefali gibi genellikle ikinci ve erken üçüncü trimesterde belirgin hâle gelen MSS anomalilerinin geç terminasyonlardaki sıklığı daha fazladır (11) .…”
Section: Discussionunclassified
“…Türkiye'de yapılan önceki çalışmalarla kıyaslandı-ğında, NTD' ye bağlı geç terminasyon sıklığı azalır-ken, NTD dışı anomalilerin sıklığında artış gözlendi (2,8) . Fakat diğer ülkelerin verileri ile kıyaslandığında NTD nedeniyle uygulanan geç terminasyon oranı yine de belirgin olarak yüksekti (4,9,14) .…”
Section: Discussionunclassified
“…Several methods of feticide have been described, [6][7][8][9][10][11] including intracardiac or intraumbilical potassium chloride or lignocaine injection to induce cardiac asystole. For women who choose to terminate pregnancy with an abnormal fetus at an advanced gestation, the method used must be safe and effective.…”
mentioning
confidence: 99%